Tooth Profile Synthesis and Meshing Force Characteristic of Sinusoidal Double Generating-wave Pushrod Movable Tooth Transmission - Wang Lichuang; An Zijun (Jixie chuandong)
Aiming at the new double sinusoidal generating wave pushrod movable tooth drive， the tooth profile synthesis and meshing force characteristic analysis are carried out. Firstly， according to the structure and the transmission principle， the profile of double sinusoidal generating-wave is designed， the tooth profile equation of center gear and the variable curvature calculation formula is deduced. According to the curvature curve of the tooth profile of center gear， the condition that the tooth profile of center gear does not interfere is gotten， and the factors to affect the actual tooth profile interference of the center gear are analyzed. Then， the changing law and the influencing factors of the meshing force on the meshing pair of the movable tooth are analyzed based on the deformation coordination relationship. The maximum meshing force of the pushrod movable tooth on the center gear and the generator is gotten respectively. Finally， the calculation formula of the pressure angle of the transmission mechanism is conducted， and the variation law and influencing factors of pressure angle are analyzed. The results show that the transmission ratio is the main factor affecting the actual profile interference of the center gear， and the amplitude is the second. The amplitude is the main factor affecting the meshing forces， and the radius of the base circle ρ0 that forms the theoretical profile of the double sinusoidal generating-wave cam is the second. The amplitude is the main factor affecting the pressure angle α1， and the ρ0 is the main factor affecting the pressure angle α2. A theoretical basis for the design and performance analysis of this mechanism is provided by this study.